Pendayagunaan Dana ZIS Untuk Operasional Ambulance Gratis Di BAZNAS Rembang - Sari, Nita (ZISWAF, 2018)
The purpose of this study is to find out how the utilization of zakat, infaq and alms in BAZNAS Rembang for free ambulance operation and to know the obstacles and solutions in the implementation of free ambulance operational program in BAZNAS Rembang. This research uses qualitative method described descriptively with field research approach (field research). The results show that ZIS funds in BAZNAS Rembang are empowered through the program of orphan and poor benefit, the development of Islam, educational scholarship, rehap house unfit for habitation, revolving capital and ambulance and its operation for free. The utilization of ZIS fund for free ambulance operation in BAZNAS Rembang includes driver, fuel, oil, toll road cost, car wash, replacement of spare parts, renewal STNK, service, and repair cost in case of accident. Constraints and solutions in the implementation of the free ambulance operational program in BAZNAS Rembang is the uneven distribution of ambulance cars, the solution that must be done is to increase fundraising of ZIS funds to increase the number of ambulances.